2019
DOI: 10.3892/mmr.2019.9830
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑18b acts as an oncogene in gastric cancer by directly targeting Kruppel‑like factor 6

Abstract: Gastric cancer (GC) is the fourth most frequently occurring cancer and the second most common cause of cancer-associated mortality worldwide. An increasing number of studies have reported that microRNAs (miRNAs/miRs) contribute to the regulation of GC development and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…KLF6 is initially considered as a tumor suppressor in prostate cancer, and is regulated through activating CDHL promoter (Tian et al 2020). Additionally, the above tumor suppressive function of KLF6 is further confirmed in hepatocellular carcinoma and gastric cancer, and is related to the effect of cell differentiation (He et al 2017;Luo et al 2019;Tian et al 2019). In this study, KLF6 was reduced in GCC cells, and was a target of miR-200c-3p confirmed by dual-luciferase reporter assay, which were consistent with the bioinformatic prediction.…”
Section: Discussionsupporting
confidence: 85%
“…KLF6 is initially considered as a tumor suppressor in prostate cancer, and is regulated through activating CDHL promoter (Tian et al 2020). Additionally, the above tumor suppressive function of KLF6 is further confirmed in hepatocellular carcinoma and gastric cancer, and is related to the effect of cell differentiation (He et al 2017;Luo et al 2019;Tian et al 2019). In this study, KLF6 was reduced in GCC cells, and was a target of miR-200c-3p confirmed by dual-luciferase reporter assay, which were consistent with the bioinformatic prediction.…”
Section: Discussionsupporting
confidence: 85%
“…The importance of miRNAs in prognosis, diagnosis, and treatment as well as drug resistance of GI cancer has been widely reported. [14][15][16][17] Recently, accumulating evidence has indicated that a variety of miRNAs could target CD molecules in GI cancers, thereby modulating the cancer progression. Using the Gene Expression Omnibus database and RNA-Seq colon cancer data from The Cancer Genome Atlas data portal, Gao et al 18 reported that CD92 was targeted by miR-183, miR-206, and miR-147 in colon cancer, and differentially expressed genes (DEGs) were identified between colon tumor samples and adjacent normal samples.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Cancer therapy may benefit greatly from the study of microRNAs. It's well-known that miRNAs are known to affect prognosis, diagnosis, therapy, and medication resistance of GI cancer [34][35][36][37][38][39]. We outlined the most recent research on miR-34a functions in GI cancers in this review.…”
Section: Cancer Cell Internationalmentioning
confidence: 99%